Sustainable aquaculture development in floating nets at Cirata reservoir (West Java, Indonesia) through single-sex nilem fish introduction - AYI YUSTIATI; YULI ANDRIANI; TITIN HERAWATI (Asian Journal of Agriculture, 2017)
Abstract. Yustiati A, Andriani Y, Herawati T. 2017. Sustainable aquaculture development in floating nets at Cirata reservoir (West Java, Indonesia) through single sex nilem fish introduction. Asian J Agric 1: 29-34. This research aimed to develop a sustainable aquaculture system using single-sex nilem fish (Osteochilus hasseltii Valenciennes, 1842; syn. Osteochilus vittatus Valenciennes, 1842) in trophic level-based farming and to analyze the feeding habits, types of meal and preference level of the feed in O. vittatus farmed in Cirata Reservoir. In addition, it also aimed to determine the fish's ability as a biocontrol agent for water cleaning by measuring the ability to utilize periphyton attached to the floating nets. Research was conducted at the Laboratory of Ciparanje, Faculty of Fisheries and Marine Sciences, Universitas Padjadjaran and floating nets of Cirata reservoir. Observations of the performance of biological testing and food feeding were applied with the experimental design method of Completely Randomized Design (CRD) consisting of 5 treatments and 3 replications. The five treatments include non-artificial feeding (treatment A), 1% feeding of body weight per day (treatment B), 2% feeding of body weight per day (treatment C), 3% of feeding of body weight per day (treatment D), and 4% feeding of body weight per day (treatment E). The results showed there was no difference in both the survival and growth levels of the female single-sex fish that were given both commercial and non-commercial feed. The highest feed efficiency was observed in the 3% of commercial feeding treatment, amounting to 55.30%. The fish are herbivorous and generalist with trophic levels between 1.03% and 1.45% eating plankton for living. Fish fed with artificial food to 4% of the biomass still grazed on phytoplankton as the main source of food but adapted by changing the natural feeding and tend to be ineffective in utilizing the available food resources in the waters. During the study, both the types and amount of periphyton attached to the nets decreased. Higher commercial feeding level results in a higher density of periphyton in the floating nets.